2015
DOI: 10.1364/ol.40.002688
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced optical Hall effect in two-dimensional free charge carrier gases detected at terahertz frequencies

Abstract: The effect of a tunable, externally coupled Fabry-Pérot cavity to resonantly enhance the optical Hall effect signatures at terahertz frequencies produced by a traditional Drude-like two-dimensional electron gas is shown and discussed in this communication. As a result, the detection of optical Hall effect signatures at conveniently obtainable magnetic fields, for example by neodymium permanent magnets, is demonstrated. An AlInN/GaN-based high electron mobility transistor structure grown on a sapphire substrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Details on the THz OHE methodology can be found in Ref. [8]. Ellipsometric data was acquired and analyzed using the Stokes vector formalism which describes the sample optical response via a 4x4 Mueller matrix [9].…”
mentioning
confidence: 99%
“…Details on the THz OHE methodology can be found in Ref. [8]. Ellipsometric data was acquired and analyzed using the Stokes vector formalism which describes the sample optical response via a 4x4 Mueller matrix [9].…”
mentioning
confidence: 99%
“…Furthermore, the gas cell is equipped with a high-grade neodymium permanent magnet with a surface field of B = 0.55 T Tesla for in-situ optical Hall effect measurements (see Sec.V-D). Figure 3 c) depicts a newly designed air-gap-manipulator sample stage for cavity-enhanced and cavity-enhanced optical Hall effect measurements [42]. The air-gap manipulator sample stage allows for opening an air gap between a highly reflective (metal) surface and the backside of the sample.…”
Section: ) System Add-onsmentioning
confidence: 99%
“…The OHE allows for detection of three free charge carrier parameters, charge density, charge mobility and effective mass [54][55][56][57][58]. The magnitude of the OHE birefringence can be further tuned by adding a cavity with varying thickness on the backside of a (transparent) sample [42,59,60].…”
Section: Terahertz Optical Hall Effect (Thz-ohe)mentioning
confidence: 99%
“…It has been shown that the use of a backside cavity with a highly reflective backside surface can enhance the OHE in HEMT structures and EG, as a result of the formation of Fabri-Pérot modes, within the sample-cavity system [37][38][39]. An optical scheme of the cavity-enhanced (CE)-OHE measurement for a sample containing a transparent substrate and a conductive layer on top is shown in Figure 1.3.…”
Section: Cavity-enhanced Optical Hall Effectmentioning
confidence: 99%